Selective switching of multiple plexcitons in colloidal materials: directing the energy flow at the nanoscale. Issue 12 (12th March 2021) - Peruffo, Nicola; Gil, Gabriel; Corni, Stefano; Mancin, Fabrizio; Collini, Elisabetta
Abstract : Two sets of plexcitonic resonances are selectively activated and connected by a relaxation cascade in colloidal particle-porphyrin nanosystems. Abstract : Coupling of molecular emitters to plasmon resonances in metal nanostructures has long been investigated to control the light–matter interaction at the nanoscale. The emergence of different coupling behaviors can be governed by the various combinations of emitters and plasmonic substrates, as well as the spatial arrangement of the individual components. Here colloidal assembly methods are exploited to prepare a responsive nanosystem where two sets of plexcitonic resonances in different coupling regimes can be selectively switched on and off, acting on external conditions such as concentration and presence of anions. The two sets of plexciton resonances are built exploiting the strong coupling between cationic gold nanoparticles and the same molecular moiety, an anionic porphyrin, in different aggregation states. When both plexciton resonances are simultaneously activated in the system, evidence for a plexciton relaxation cascade has been found in photoluminescence experiments. These findings have fundamental implications for achieving control over energy flow at the nanoscale.